Development of Press Machine For Metal Waste Using Blynk Application Remote Control At General Machine Workshop - Rubani, Siti Nur Kamariah; Mohd Nazri Kamis; Normah Zakaria; Norhasyimah Hamzah; Arihasnida Ariffin (Research and Innovation in Technical and Vocational Education and Training, 2021)
This study is related to the development of a press machine for metal waste using Blynk application remote control at general machine workshop. The purpose of product development was to manage the metal waste and storage space. The press machine was capable of compressing metal waste into cube blocks. Therefore, the wasted metal could be stored in proper places. The compressor of the press machine could be controlled using remote ESP8266 which was connected to the Blynk android application. The waterfall model was used as a guideline for the development of the product. The analysis was carried out by using product testing to test the suitability using pneumatic systems as a compressor and functionality application ESP8266. The result of testing showed that the press machine could work for the metal waste in the machine shop.